Investment appeal evaluation of a public company by a retail investor : a case study of LVMH stock - Nikolaev, Stepan; Jurek, Martin; Stasa, Michele; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The paper investigates how an unexperienced retail investor can decide whether to buy or to sell shares of a company, which tools and ratios to use for this evaluation, and which factors to consider. LVMH is worth researching as it is a large company that is popular among investors (with free-float of over 50%). For that purpose, important theoretical works were studied, and calculations were made based on data found in financial statements. The latest articles and research on the company were also studied, as they might contain insights into future prospects of the business. The results shed light on how to build an investment strategy that is entirely accessible to an inexperienced investor using a set of general financial ratios that can easily be calculated based on open access data. Although these ratios are of a retrospective nature, they can still be helpful when deciding on the purchase or sale of shares. To increase their awareness and to understand the broader picture, investors should make use of additional tools, including news analysis and elements of predictive analytics (e.g., to make prognoses regarding macroeconomic and business outlook).
Vedoucí práce: Martin Jurek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses